2012
DOI: 10.1002/mc.21977
|View full text |Cite
|
Sign up to set email alerts
|

Human MCS5A1 candidate breast cancer susceptibility gene FBXO10 is induced by cellular stress and correlated with lens epithelium-derived growth factor (LEDGF)

Abstract: Genetic variation and candidate genes associated with breast cancer susceptibility have been identified. Identifying molecular interactions between associated genetic variation and cellular proteins may help to better understand environmental risk. Human MCS5A1 breast cancer susceptibility associated SNP rs7042509 is located in F-box protein 10 (FBXO10). An orthologous Rattus norvegicus DNA-sequence that contains SNV ss262858675 is located in rat Mcs5a1, which is part of a mammary carcinoma susceptibility locu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…However, in this study and another study by one of our laboratories, we find that translated cFos can bind to the distal site as either a homodimer or a monomer (Xu et al, 2014). We showed that tBHQ-induced expression of CYP2C9 is mediated possibly by interaction between cFos and JunD on different AP-1 sites.…”
Section: Discussionsupporting
confidence: 43%
“…However, in this study and another study by one of our laboratories, we find that translated cFos can bind to the distal site as either a homodimer or a monomer (Xu et al, 2014). We showed that tBHQ-induced expression of CYP2C9 is mediated possibly by interaction between cFos and JunD on different AP-1 sites.…”
Section: Discussionsupporting
confidence: 43%
“…65). In support of this notion, there is pathological evidence indicating that low expression levels of FBXO10 were tightly associated with breast cancer risk 6668 . Similarly, FBXO18 is often deleted or mutated in melanoma cells, and the depletion of FBXO18 enhances ultraviolet (UV)-mediated transformation of human melanocytes, which suggests a tumoursuppressive role of FBXO18 (REF.…”
Section: Tumour-suppressive F-box Proteinsmentioning
confidence: 83%
“…In addition, LEDGF/p52 has been associated with splicing through its interaction with serine/arginine-rich splicing factor 1 (SRSF1) 1,5 . Currently it is not clear whether the previously proposed roles of LEDGF/p75 in apoptosis and stress response, as well as its increased expression levels in different cancer types, are related to one of these functions [6][7][8][9][10][11] .…”
mentioning
confidence: 99%